The Challenges Facing Distance School Education in Some Arab Countries and Their Solutions during Corona Pandemic According to Teachers and Supervisors Perspectives - Almomani, Jehad Ali (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the challenges that face distance school education in the Arab world and their solutions during Corona pandemic from teachers and supervisors perspectives. The sample consisted of (40) teachers and educational supervisors who were chosen from (7) Arab countries. The study followed the qualitative descriptive approach. To achieve the goal of the study, an open-ended electronic questionnaire was made, which was applied to a selected sample by the available random method, which consisted of (40) teachers and educational supervisors chosen from (7) Arab countries. The results showed that the most prominent challenges of distance school education, agreed upon by 90% of them, were represented in the academic side by the weak experience in dealing with technology, the weak motivation of students for distance learning and the difficulty of their assessment and taking into account the individual differences between them, and in the social and family side represented in the weakness of family communication with the educational institution and the lack of follow-up to their children, and the difficulty of providing an educational environment suitable for them for distance learning, and in the psychological aspect was the increase in the psychological pressure of the family, and the students’ feeling of frustration and anxiety over their future, while on the economic side, the most prominent challenges were represented in increasing the financial burdens of the family to provide the requirements of distance learning And the high prices of electronic devices and the Internet, and on the technical side, it was represented in the lack of qualified technical cadres for all those concerned with school education, while 40% of them indicated other challenges for distance learning, most notably the increase in the number of students, the low educational level of parents, and the inappropriateness of the current curricula. for distance learning. As for the appropriate solutions to these challenges, 90% of them indicated that the most prominent solutions to these challenges were the development of the infrastructure for distance education and the provision of appropriate educational platforms, as well as the provision of rehabilitation training programs for educational and technical cadres, as well as psychological counseling programs to support and increase students’ motivation. For learning 50% of them indicated the need to apply blended learning or return to face-to-face learning completely to ensure the continuity of learning.